2022
DOI: 10.3389/fimmu.2022.986359
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant immunotherapy and chemoimmunotherapy for stage II-III muscle invasive bladder cancer

Abstract: ObjectiveConsidering the striking evidence revealed by immunotherapy in advanced or metastatic bladder cancer, investigators have explored neoadjuvant immunotherapy and chemoimmunotherapy in muscle-invasive bladder cancer (MIBC). Currently, there have been a large number of studies reporting varied efficacy and safety of these approaches. Herein, we pooled the available evidence in terms of oncological outcomes (pathological complete response [pCR] and pathological partial response [pPR]) and safety outcomes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 69 publications
0
18
0
1
Order By: Relevance
“…Compared to ICI alone, the addition of chemotherapy can release large amounts of tumor antigen and boost the effect of effector lymphocytes (31). However, we should bear in mind that the improved response rate and prolonged survival may be at the cost of increased morbidity of adverse effects (32). Urologists and oncologists should balance the benefits and harms of combination therapy for BCa patients of high IRS.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to ICI alone, the addition of chemotherapy can release large amounts of tumor antigen and boost the effect of effector lymphocytes (31). However, we should bear in mind that the improved response rate and prolonged survival may be at the cost of increased morbidity of adverse effects (32). Urologists and oncologists should balance the benefits and harms of combination therapy for BCa patients of high IRS.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few decades, the advent of immunotherapy has remodeled the treatment paradigm and accelerated the development of individualized precision therapy for cancers. The immunotherapy, such as PD-1, PD-L1, and CTLA-4 inhibitors, has improved the prognosis of BCa patients but is still in the initial stage, and more clinical trials in multi-center are urgently needed [ 5 , 35 ]. The existing body of studies on m7G suggested that its abnormal expression would heighten the translation of oncogenic mRNAs and boost tumorigenesis, advancement, and metastasis in various cancers, especially in BCa [ 13 15 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite undergoing standard treatment, 31%–78% of NMIBC patients relapse within five years. Additionally, 10%–30% of NMIBC patients will ultimately progress to MIBC, which requires a more aggressive approach involving radical cystectomy and chemotherapy 3–6 . Unfortunately, some people with MIBC still face poor survival rates even with these treatments 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 10%-30% of NMIBC patients will ultimately progress to MIBC, which requires a more aggressive approach involving radical cystectomy and chemotherapy. [3][4][5][6] Unfortunately, some people with MIBC still face poor survival rates even with these treatments. 7 The increase in publicly available RNA-seq datasets and advanced bioinformatic toolkits have enabled the discovery of numerous new molecular biomarkers.…”
mentioning
confidence: 99%